Analyses of multiple single-nucleotide polymorphisms in the SUMO4/IDDM5 region in affected sib-pair families with type I diabetes - Podolsky, R (2009)
Previous studies suggested that the SUMO4 gene, located in the IDDM5 interval on chromosome 6q25, was associated with type I diabetes (T1D) and several other autoimmune diseases. Subsequent analyses of the SUMO4 variants with T1D suggested that the association was stronger and more consistent in the Asian populations. In addition, considerable heterogeneity has been observed in the Caucasian populations. In this report, a 40-kb genomic interval including the SUMO4 gene was tagged with 15 single-nucleotide polymorphisms. A total of 2317 affected sib-pair families from the Type I Diabetes Genetic Consortium were genotyped using both the Illumina and Sequenom genotyping platforms. In these Caucasian families, we found little evidence supporting an association between SUMO4 and T1D.